Profilometry-based indentation plastometry to obtain stress-strain curves from anisotropic superalloy components made by additive manufacturing - Tang, YT; Campbell, JE; Burley, M; Dean, J; Reed, RC; Clyne, TW (Elsevier, 2021)
This investigation concerns superalloy samples produced by an additive manufacturing procedure. Microstructural examination confirmed that they exhibited a columnar grain structure, with the grains elongated in the growth (“build”) direction and exhibiting a strong texture involving alignment of 〈100〉 parallel to this axis. Samples were tensile tested along both build and transverse directions, being found to be both stiffer and harder in the latter. This material thus exhibits well-characterized anisotropy, making it well-suited to study of how this affects outcomes from an indentation-based procedure for obtaining stress-strain curves. This is termed Profilometry-based Inverse FEM for Plasticity Parameters from Indentation (PIP). True stress-strain curves obtained using this methodology were found to be entirely consistent with the directly-measured curves. Furthermore, it is shown that full 3-D characterization of the indent profiles can be used to obtain at least a semi-quantitative indication of the nature and strength of the plastic anisotropy. This constitutes a significant advance in the context of a technique that could have a transformative effect on mechanical testing procedures.